Challenges in Virtual Collaboration Videoconferencing, Audioconferencing, and Computer-Mediated Communications - Wainfan, Lynne (RAND Corporation, 2004)
A summary of the research literature on how the processes and outcomes of virtual, or mediated, collaborations are affected by the communication medium (videoconferencing, audioconferencing, or computer-mediated conferencing); a discussion of ways to mitigate problems in such collaboration; and a suggested strategy for choosing the most effective medium, including face-to-face communication and hybrid systems, as a function of task and context.